2019
DOI: 10.1101/609115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Requirements for the RAD51 Paralogs in Genome Repair and Maintenance in Human Cells

Abstract: Deficiency in several of the classical human RAD51 paralogs [RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3] is associated with cancer predisposition and Fanconi anemia. To investigate their functions, isogenic disruption mutants for each were generated in non-transformed MCF10A mammary epithelial cells and in transformed U2OS and HEK293 cells. In U2OS and HEK293 cells, viable ablated clones were readily isolated for each RAD51 paralog; in contrast, with the exception of RAD51B, RAD51 paralogs are cell-essential in M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 108 publications
(145 reference statements)
2
4
0
Order By: Relevance
“…Importantly, and in agreement with previous reports (32), RAD51B inactivation resulted in a more modest reduction in RAD51 foci formation both in SKOV3 and DU145 cells despite efficient DNA damage induction ( Fig 2C-D ), consistent with the reduced sensitivity of RAD51B KO cells to olaparib treatment. Also as previously reported, RAD54L deficiency led to an increase in RAD51 foci formation ( Fig 2D ), which has been linked to the impaired removal of RAD51 molecules upon resolution of HRR and/or the increased number of RAD51 pre-synaptic complexes required to find homology on themdonor DNA strand (35,36).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Importantly, and in agreement with previous reports (32), RAD51B inactivation resulted in a more modest reduction in RAD51 foci formation both in SKOV3 and DU145 cells despite efficient DNA damage induction ( Fig 2C-D ), consistent with the reduced sensitivity of RAD51B KO cells to olaparib treatment. Also as previously reported, RAD54L deficiency led to an increase in RAD51 foci formation ( Fig 2D ), which has been linked to the impaired removal of RAD51 molecules upon resolution of HRR and/or the increased number of RAD51 pre-synaptic complexes required to find homology on themdonor DNA strand (35,36).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, from the list of 110 confidence genes, XRCC3 was the most frequently altered gene in our analyses specifically in PARPi-approved settings ( Fig 3A, C ). XRCC3 is one of the five RAD51 paralogs encoded in the human genome (the others being RAD51B, RAD51C, RAD51D and XRCC2) and its function in HRR is well described (32). Accordingly, statistical analyses of the most altered genes in our dataset showed that LoF of XRCC3 is mutually exclusive with either BRCA1 (Fisher’s exact p value 0.002) or BRCA2 (Fisher’s exact p value 0.01) LoF when considering the pan-cancer dataset ( Supp Fig S4A-B ), an effect that becomes even more significant when limiting the analysis to ovarian, breast, pancreatic and prostate tumours ( BRCA1 p value 4.1E-07; BRCA2 p value 6.4E-04; Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are a number of DNA repair genes that are misspliced and/or inefficiently exported for translation in SF3B1 K700E cells, including EME1 and XRCC3, which both exhibit increased alternative 3' splice site usage (Figure S5B-C). Notably, both genes have been previously shown to be important for HR downstream of Rad51 loading (34,35) although, it remains to be determined whether the DSB repair abnormalities observed in cells expressing SF3B1 K700E arise directly from aberrant splicing of either of these genes.…”
Section: Discussionmentioning
confidence: 99%